Survival rate and neurodevelopmental outcome of extremely premature babies: an 8-year experience of an Italian single neonatal tertiary care center - Sara Uccella; Agnese De Carli; Ida Sirgiovanni; Paola Schiavolin; Giuseppe Damiano; Beatrice Ghirardi; Francesca Maglioli Carpano; Laura Bassi; Silvana Gangi; Odoardo Picciolini; Monica Fumagalli; Fabio Mosca (PAGEPress Publications, 2015)
Extremely preterm babies are at major risk for adverse neurodevelopmental outcome, being the gestational age (GA) the main determinant for a good-quality survival. Aim of this retrospective study was to investigate the neurodevelopmental outcome in a population of extremely preterm babies admitted to a single neonatal tertiary care unit over an 8-year period. All babies born between 23+0 and 25+6 weeks of GA from January 2003 until December 2010 were retrospectively enrolled. Perinatal and neonatal variables were recorded. Motor and cognitive development was assessed using the neurofunctional scale (NFS) and the Griffith's scales at 2 years. Fifty-five out of 122 infants survived to discharge. Survival rates doubled for each additional gestational week from 23 to 25: 16%, 38% and 74% at 23, 24 and 25 weeks GA respectively. Forty-six infants were evaluated at 2 years. A poor cognitive and motor outcome was observed in all babies born at 23 weeks. Griffith's general quotient (GQ) was ≥76 in 62% and ≥88 in 33% of babies born between 24 and 25 weeks. No severe motor disabilities were found in 81% of babies born between 24 and 25 weeks. Preterm premature rupture of membranes, absence of prenatal steroids, intrauterine growth restriction, male, lower GA and major brain abnormalities at magnetic resonance imaging (MRI) were significantly associated with worse NFS and lower mean GQ at 2 years of age. GA, gender and abnormal MRI findings remained significantly associated with impaired NFS at the multivariate analysis. Survival rates and neurodevelopmental outcome improved with each week of GA. These results are relevant for clinicians counselling families facing an unavoidable extremely preterm birth.